Assessment of the healing activity of polyelectrolyte complexes through molecular and histological characterization. (6th December 2016) - Mahdy, Elsayed M; El-mezayen, Hatem A; Eldegheidy, Eglal; Alsharabasy, Amir M
Abstract: Wound dressings based on composites of polymers are widely used for activating the healing process, but the expression of genes related to the growth of new tissue during healing, activated by these dressings has not been widely investigated. This study examined the effects of polyelectrolyte complex (PEC) made of the alginate and chitosan biomaterials in the form of hydrogel on the healing of excision wound. This was through studying of the changes in the expression of two angiogenic genes (vascular endothelial growth factor (VEGF) and Von Willebrand factor (vWF)) during the healing progress with real time polymerase chain reaction supported by assessing the accompanied histological changes within the healing wounds. Complete healing was observed after 16 days of the hydrogel application, but no complete closure was observed for the non-treated wounds even after three weeks of healing. The VEGF expression was enhanced in the treated wounds to reach its maximum by the 7th day referring that the two polyelectrolytes within the complex could maintain the angiogenic cascade for accelerated wound closure as well as its possible usage as a marker for enhanced neo skin tissue growth. In contrast, there were low expression levels of the vWF gene in blood cells during the first week of healing of the treated wounds, which began then to increase along with the decreasing of VEGF expression which may be due to the hemostatic effects of the used complex in the wound area. This may prove the efficiency of the hydrogel with its PEC structure in the treatment of acute wounds with accelerating the supply of blood vessels for neo tissue growth.